Design of a Four-Element Array Antenna for 5G Cellular Wireless Networks - My, D. T. T.; Phuong, H. N. B.; Huong, T. T.; Tu, B. T. M. (Engineering, Technology & Applied Science Research, 2020)
This paper proposes the design of a four-element array planar antenna based on a single antenna that combines the Double Positive (DPS) and Epsilon Negative (ENG) materials. The single antenna consists of a microstrip segment (which is equivalent to a DPS material) connected to a grounded microstrip segment (which is equivalent to an ENG material). T-Junction power dividers with one-input and two-output ports are used for feeding the two-element and the four-element array antennas. The proposed array antenna is designed to operate optimally at 30GHz frequency under Finite Element Method (FEM)-based simulation. The obtained simulation results show that the proposed array antennas have good radiation performances, in which the four-element array antenna has a -10dB bandwidth ranging from 28.7 to 33.4GHz and 12.9dBi gain.